Effect of Training, Encouragement Family, Social and Environmental Decision against Formal Education Entrepreneurship The Entrepreneurship Motivation as an intervening variable (A Study on the Job Search on Social Services, Manpower and Transmigration Ka - Sarwosih, Isti Titi (STIE AUB Surakarta)
This study aims to identify and analyze the Influence of training, encouragement family, social environment and formal education against the decision of entrepreneurship with entrepreneurship motivation as an intervening variable (A Study on the Job Search on Social Services, Manpower and Transmigration Karanganyar).The population is looking for work in the Social Service Manpower Karanganyar in the first quarter in February 2015 a number of 50 respondents. The analysis technique used is using validity and reliability test, linearity test, regression analysis, t test, F test, test the coefficient of determination, correlation analysis and path analysis. Hypothesis test results on the first equation can be concluded that: Variable Training positive and significant impact on entrepreneurship motivation. As for the variable dorongangan family and formal education and no significant positive effect on the motivation of entrepreneurship, social and environmental variables and no significant negative effect. Test results t in the second equation can be concluded that: entrepreneurship motivation variable positive and significant impact on the decision entrepreneurship and job seekers. While variable encouragement of family and formal education and no significant positive effect on the decision variable boost entrepreneurship and family and social environment and no significant negative effect. F test can be concluded jointly independent variable affecting entrepreneurship Decision jobseekers. R2 total value amounted to 0.768, can be interpreted variable entrepreneurial decision-seekers in the Social Service Manpower Karanganyar explained by the variable training, encouragement family, social environment, formal education and entrepreneurship motivation for 76.8% and the remaining 23.2% is explained other variables outside the model study as an example of technological knowledge, experience job seekers and so on. Results of path analysis showed that: The indirect effect of the decision entrepreneurship training through entrepreneurship motivation produce a greater effect than the direct effect. Indirect influence of family encouragement to the decision of entrepreneurship through entrepreneurship motivation produce a greater effect than the direct effect. Indirect influence of the social environment on the decision entrepreneurship through entrepreneurship motivation produce a greater effect than the direct effect. indirect influence on the decision-formal education in entrepreneurship through entrepreneurship motivation produces a smaller effect than the direct effect.Â Keywords : Training, Encouragement Family, Social Environment, Formal Education, Motivation Entrepreneurship, Entrepreneurship Decision